Are Dietitians With Obesity Perceived as Competent and Warm? Applying the Stereotype Content Model to Weight Stigma in Brazil - Cassiano, Giovana Santarosa; Carvalho-Ferreira, Joana Pereira; Buckland, Nicola J.; Ulian, Mariana Dimitrov; da Cunha, Diogo Thimoteo (Frontiers in Nutrition, 2022)
The aim of this study was to understand how dietitians’ body size influences perceived competence and warmth, based on the Stereotype Content Model (SCM). Online data were collected from 1,039 Brazilians, who were either laypeople, registered dietitians, or nutrition students. Participants rated the competence and warmth dimensions of three dietitians who differed in sex, body weight, and age. Participants also indicated how likelythey would consult or recommend each dietitian for nutritional advice, and indicated their attitudes towards people with obesity [using The Antifat Attitudes Test (AFAT)]. Laypeople attributed less competence and warmth to all profiles compared to dietitians and students (p < 0.001). Three clusters occupied the SCM warmth-by-competence space. However, the clusters were different among groups (laypeople, dietitians, and students). For lay participants, the woman without overweight, the older woman, and the older man were located in the high competence/ medium warmth cluster. Meanwhile, the woman with obesity was located in the medium competence / high warmth cluster. The dietitians and students map found the woman with obesity and the older woman in a high competence and warmth cluster. In general, the woman with obesity, the man without obesity, and the older man can be classified as ambivalent stereotypes, the woman being perceived as more warm than competent and the men more competent than warm. Participants with high AFAT scores were less likely to consult or recommend to a family member a dietitian with obesity. This study contributes to identifying ambivalent stereotypes for dietitians. Dietitians with obesity can be seen as warm but less competent. Also, although less intense than laypeople, dietitians and students exhibited weight stigma. These findings can foster important discussions about weight stigma and emphasize the need to increase population awareness about the causes of obesity.